Rehabilitasi Pasca Total Knee Arthroplasty - Putu Duhita Ayuningtyas W (PT Kalbe Farma Tbk., 2019)
Total Knee Arthroplasty (TKA) merupakan pilihan terapi terbaik untuk pasien osteoartritis lutut stadium akhir. Keberhasilan TKA juga ditentukan oleh rehabilitasi adekuat untuk mengembalikan fungsi sendi setelah operasi. Rehabilitasi setelah TKA berfokus pada pemulihan range of motion (ROM) sendi, mengembalikan kekuatan otot lutut dan panggul, mengembangkan fungsi kemandirian dan kemampuan berpartisipasi dalam kegiatan rekreasi. Tujuan tersebut dapat dicapai melalui kombinasi modalitas rehabilitasi meliputi exercise therapy, latihan keseimbangan, aquatic therapy, terapi es atau kompresi, continuous passive motion (CPM), transcutaneous electrical nerve stimulation (TENS), neuromuscular electrical stimulation (NMES), dan instrument-assisted soft-tissue therapy. Total knee arthroplasty (TKA) is an excellent option for end-stage knee osteoarthritis. Its success also depend on the adequacy of rehabilitation to restore functional ability following surgery. Rehabilitation after TKA focuses on recovery of knee range of motion (ROM), restoration of knee and hip muscle strength, development of functional independence, and the ability to participate in recreational activities. It can be achieved by combination of modalities such as exercise therapy, balance training, aquatic therapy, cold therapy and compression, continuous passive motion (CPM), transcutaneous electrical nerve stimulation (TENS), neuromuscular electrical stimulation (NEMS), and instrument-assisted soft-tissue therapy.